Morphological and immunophenotypical properties of chicken bone marrow-derived dendritic cells towards wild type and H5-recombinant fowlpox virus infections - Mohamad Abir, Anis Suraya; Yusof, Sakinah; Abd Rahaman, Yasmin; Omar, Abdul Rahman; Ho, Kok Lian; Tan, Wen Siang; Mariatulqabtiah, Abdul Razak (ResearchersLinks, 2022)
Fowlpox is a common viral disease caused by fowlpox virus (FWPV), which infects birds. Fowlpox is an important disease in commercial poultry farming, as it can affect many production-system variables, such as size, performance and viability. Studies on the interactions between chicken bone marrow-derived dendritic cells (chBM-DCs) and FWPV and its recombinant viruses are limited compared to other avian viral infectious diseases. Therefore, this study characterised the response of chBM-DCs to infection with the wild-type (WT) FP9 strain of FWPV compared to a recombinant FWPV carrying the H5 gene of avian influenza virus (rFWPV-H5) using morphological and immunophenotypical observations. The results showed that the rFWPV-H5-infected chBM-DCs formed better dendrites and stellate cells, compared to the WT FWPV. The recombinant virus also expressed higher levels of the surface markers CD86 and MHC class II double-positive chBM-DCs 12 and 24 h post-infection. In conclusion, chBM-DCs were susceptible to WT FWPV and rFWPV-H5 infections, where the recombinant virus induced phenotypic maturation of the cells better than the WT virus. This study supports further understanding of the innate immune response after FWPV infection in chickens.